SOCS, Intrinsic Virulence Factors, and Treatment of COVID-19 - Johnson, Howard M.; Lewin, Alfred S.; Ahmed, Chulbul M. (Frontiers in Immunology, 2020)
The suppressor of cytokine signaling (SOCS) family of intracellular checkpoint inhibitors has received little recognition compared to other checkpoint inhibitors. Two members of this family, SOCS1 and SOCS3, are indispensable, since SOCS1 knockout in mice results in neonatal death due to interferon gamma (IFN) induced inflammatory disease, and SOCS3 knockout leads to embryonic lethality. We have shown that SOCS1 and SOCS3 (SOCS1/3) function as virus induced intrinsic virulence factors for influenza A virus, EMC virus, herpes simplex virus 1 (HSV-1), and vaccinia virus infections. Other viruses such as pathogenic pig enteric coronavirus and corona virus induced severe acute respiratory syndrome (SARS) spike protein also induce SOCS virus intrinsic virulence factors. SOCS1/3 exert their viral virulence effect via inhibition of type I and type II interferon (IFN) function. Specifically, the SOCS bind to the activation loop of receptor-associated tyrosine kinases JAK2 and TYK2 through the SOCS kinase inhibitory region (KIR), which inhibits STAT transcription factor activation by the kinases. Activated STATs are required for IFN function. We have developed a small peptide antagonist of SOCS1/3 that blocks SOCS1/3 inhibitory activity and prevents virus pathogenesis. The antagonist, pJAK2(1001-1013), is comprised of the JAK2 activation loop, phosphorylated at tyrosine 1007 with a palmitate for cell penetration. The remarkable thing about SOCS1/3 is that it serves as a broad, simple tool of perhaps most pathogenic viruses to avoid innate host IFN defense. We suggest in this Perspective that SOCS1/3 antagonist is a simple counter measure to SOCS1/3 and should be an effective mechanism as a prophylactic and/or therapeutic against the COVID-19 pandemic that is caused by coronavirus SARS-CoV2.